Are Myalgic Encephalomyelitis and chronic fatigue syndrome different illnesses? A preliminary analysis. (January 2016) - Jason, Leonard A; Sunnquist, Madison; Brown, Abigail; Evans, Meredyth; Newton, Julia L
Considerable discussion has transpired regarding whether chronic fatigue syndrome is a distinct illness from Myalgic Encephalomyelitis. A prior study contrasted the Myalgic Encephalomyelitis International Consensus Criteria with the Fukuda and colleagues' chronic fatigue syndrome criteria and found that the Myalgic Encephalomyelitis International Consensus Criteria identified a subset of patients with greater functional impairment and physical, mental, and cognitive problems than the larger group who met Fukuda and colleagues' criteria. The current study analyzed two discrete data sets and found that the Myalgic Encephalomyelitis International Consensus Criteria identified more impaired individuals with more severe symptomatology.